2022
DOI: 10.3389/fmed.2022.807730
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With HIV Preventive Behavior Among Adults in Majang Zone of Gambella Region, Southwest Ethiopia

Abstract: BackgroundHIV-positive people can spread the virus through unprotected sex; however, HIV can be avoided if populations are educated about the risks. In underdeveloped nations, evidence suggests that the ABC method for HIV prevention is quite effective. As a result, the goal of this study was to determine the magnitude of HIV prevention behavior among adults in the Majang zone of Southwest Ethiopia, as well as the factors that influence it.MethodsA community-based cross-sectional study was carried out from Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
3
2
1
Order By: Relevance
“…The current study showed that participants who had good knowledge had a significant association with HIV preventive practice. This study finding was supported by other study findings in south-west Ethiopia [16], Dima district of the Gambella region [29], Gambella town [21], Majang zone-Gambella region [30], Afar region [31], Jigawa State, Nigeria [32], and Indonesia [33]. This might be due to the fact that good knowledge will produce good behavior, and people who are aware of HIV/AIDS will act responsibly when engaging in sexual activity [33].…”
Section: Plos Global Public Healthsupporting
confidence: 86%
“…The current study showed that participants who had good knowledge had a significant association with HIV preventive practice. This study finding was supported by other study findings in south-west Ethiopia [16], Dima district of the Gambella region [29], Gambella town [21], Majang zone-Gambella region [30], Afar region [31], Jigawa State, Nigeria [32], and Indonesia [33]. This might be due to the fact that good knowledge will produce good behavior, and people who are aware of HIV/AIDS will act responsibly when engaging in sexual activity [33].…”
Section: Plos Global Public Healthsupporting
confidence: 86%
“…Younger students were more likely to have poor HIV/AIDS preventive behaviors than older students. This is similar to the study conducted in the Majang zone of the Gambella region, Ethiopia [ 2 ], but contradicts the study conducted among college students in Gambella town [ 13 ]. The discrepancy between these two studies might be due to sample size differences and the sociodemographic characteristics of the participants.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, the current study is lower than previous studies conducted in the bench-maji zone of southern Ethiopia [ 15 ] and the majang zone of the Gambella region [ 2 ]. This discrepancy might be because participants in the current study had better information about the problem since it is part of their curriculum.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations